2023
DOI: 10.21873/anticanres.16306
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value ofKRASExon-specific Mutations in Patients With Colorectal Cancer

Abstract: Background/Aim: The clinical significance of many RAS-family mutations in colorectal cancer (CRC) remains unclear. The purpose of this study was to investigate the relationship of RAS mutations on an exon basis (i.e., mutations in KRAS exons 2,3, and 4 and in NRAS) with clinicopathological features and prognosis in CRC. Patients and Methods: We performed a retrospective cohort study of the medical records and frozen tissue samples of 268 consecutive patients with stage I-III CRC who underwent curative resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…It has been reported that overexpression of CERS4 and CERS6 in colon cancer cells induced the production of short-chain ceramides (C16: 0, C18: 0 and C20: 0 ceramides), weakened cell proliferation and promoted apoptosis 23 . This is consistent with the poor prognosis of G12V and G12C mutation colorectal cancers we reported compared to wild-type KRAS colorectal cancers 12 , 13 . The present finding that CERS4 functions as an important regulator of KRAS mutation, may suggest its potential use as a marker for CRC and may also guide the development of new drugs for CRC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been reported that overexpression of CERS4 and CERS6 in colon cancer cells induced the production of short-chain ceramides (C16: 0, C18: 0 and C20: 0 ceramides), weakened cell proliferation and promoted apoptosis 23 . This is consistent with the poor prognosis of G12V and G12C mutation colorectal cancers we reported compared to wild-type KRAS colorectal cancers 12 , 13 . The present finding that CERS4 functions as an important regulator of KRAS mutation, may suggest its potential use as a marker for CRC and may also guide the development of new drugs for CRC.…”
Section: Discussionsupporting
confidence: 91%
“…It is thought that cancer can develop as a consequence due to signal transduction pathways that constantly promote cell proliferation 11 . It was reported that KRAS mutation colorectal cancer has a poorer prognosis than wild-type KRAS colorectal cancer 12 , 13 . One reason is that colorectal cancer with a KRAS mutation does not respond to cetuximab, whereas patients with colorectal cancer bearing wild-type KRAS benefited from cetuximab 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The RAS mutation rate was significantly associated with age and histology. Patients with KRAS exon 2 mutations exhibited shorter recurrence-free survival than those with KRAS wild-type, KRAS exon 3 mutations, KRAS exon 4 mutations, and NRAS mutation [46].…”
Section: Raf Gene Familymentioning
confidence: 90%
“…In recent years, there has been a widespread acknowledgment that the prognosis of cancer patients is intricately connected to either the characteristics of the tumor or numerous host-related factors (2,3). Notably, tumor characteristics, speci cally the presence of KRAS G12V or G12C mutations, have been reported to correlate with a poorer prognosis in colorectal cancer (4,5). Turning to host-related factors, there is a growing emphasis on understanding the impact of the in ammatory state on the prognosis of patients with malignant tumors.…”
Section: Introductionmentioning
confidence: 99%